Immune Reconstitution/Immunocompetence in Recipients of Kidney Plus Hematopoietic Stem/Facilitating Cell Transplants. Issue 2 (February 2015) - Leventhal, Joseph R.; Elliott, Mary J.; Yolcu, Esma S.; Bozulic, Larry D.; Tollerud, David J.; Mathew, James M.; Konieczna, Iwona; Ison, Michael G.; Galvin, John; Mehta, Jayesh; Badder, Mark D.; Abecassis, Michael M. I.; et al.
Abstract : Nineteen subjects have more than 18 months' follow-up in a phase IIb tolerance protocol in HLA–mismatched recipients of living donor kidney plus facilitating cell enriched hematopoietic stem cell allografts (FCRx). Reduced intensity conditioning preceded a kidney allograft, followed the next day by FCRx. Twelve have achieved stable donor chimerism and have been successfully taken off immunosuppression (IS). We prospectively evaluated immune reconstitution and immunocompetence. Return of CD4 + and CD8 + T central and effector memory cell populations was rapid. T-cell receptor (TCR) Excision Circle analysis showed a significant proportion of chimeric cells produced were being produced de novo. The TCR repertoires posttransplant in chimeric subjects were nearly as diverse as pretransplant donors and recipients, and were comparable to subjects with transient chimerism who underwent autologous reconstitution. Subjects with persistent chimerism developed few serious infections when off IS. The majority of infectious complications occurred while subjects were still on conventional IS. BK viruria and viremia resolved after cessation of IS and no tissue-invasive cytomegalovirus infections occurred. Notably, although 2 of 4 transiently or nonchimeric subjects experienced recurrence of their underlying autoimmune disorders, none of the chimeric subjects have, suggesting that self-tolerance is induced in addition to tolerance to alloantigen. No persistently chimeric subject has developed donor-specific antibody, and renal function has remained within normal limits. Patients were successfully vaccinated per The American Society for Blood and Marrow Transplantation guidelines without loss of chimerism or rejection. Memory for hepatitis vaccination persisted after transplantation. Chimeric subjects generated immune responses to pneumococcal vaccine. These data suggest that immune reconstitution and immunocompetence are maintained in persistently chimeric subjects. Abstract : The authors present an updated report on the phase IIb study of the important prospects for use of faciltatory/hempoetic stem cells to deliver alloimmune tolerance.